IMPLEMENTASI PERMENDIKBUD NO. 23 TAHUN 2015 TENTANG PENUMBUHAN BUDI PEKERTI PADA SISWA DI MTs. S NURHASANAH MEDAN - Anwar, Marisa; Lubis, Syukri Azwar; Harahap, Nikmah Royani (Fakultas Agama Islam Universitas Al Washliyah, 2024)
This study examines three things, namely to describe the Value of Employer Education implanted in students, describe the Implementation of Permendikbud No.23 Year 2015 on Growth of Employees (PBP) as well as to find out the Supportive and Inhibitory Factors of Implémentation of PBP No. 23 Year 2015 about Growing Employment (PbP) in students of the eighth grade in Nurhasanah Field MTs. This research is at Nurhasanah Medan MTs, located at Jl. Garu 1 No.44, Sitirejo III, Amplas Medan District, Medan City, North Sumatra 20226. The research was carried out over six months from the observation of the object to the collection of data. The type of research that the researchers use in this study is descriptive with data in words, images, and not numbers that come from interview manuscripts, field records, photos, videos, personal documents, notes, memos, and other official documents. Qualitative data analysis in this study is performed interactively and continuously continues until the end so that the data is saturated. Activities in data analysis, i.e. reduction, data display, and conclusion drawing/verification. The results of this study are: 1) The values of the education of the practitioner who is planted in the students of the eighth grade in the Nurhasanah Medan MTs are good and have been on for a long time; 2) Implementation of the permendikbud no.23 of 2015 on the growth of the employee in the pupils of the 8th grade in Nurhasanaah Medan has been done and implemented well, not only in the eighteenth grade only but in all pupils who are in the Nurhasananah Medan; and 3) the supporting factor is the environment, both the school environment such as teachers, peers and family environments such as the parents of pupils.